A mechanistic study of the effect of transferrin conjugation on cytotoxicity of targeted liposomes. (18th August 2018) - Moghimipour, Eskandar; Rezaei, Mohsen; Kouchak, Maryam; Ramezani, Zahra; Amini, Mohsen; Ahmadi Angali, Kambiz; Saremy, Sadegh; Abedin Dorkoosh, Farid; Handali, Somayeh
Abstract: This study was performed to prepare 5-fluorouracil (5FU) containing targeted liposomes for the safety and efficacy enhancement. Liposomes were prepared using thin layer method and transferrin (Tf) was employed as the targeting ligand. Morphology of 5FU-loaded liposomes was assessed by transmission electron microscopy (TEM). The in vitro cytotoxicity was investigated via MTT assay on HT-29, CT26 and fibroblast cells. Mitochondrial membrane and cell death evaluations were also investigated. Resulted showed that the encapsulation efficiency (EE%) and particle size of the liposomes were 40.12% and 130 nm, respectively. TEM image implied that liposomes were spherical in shape. In cancer cells, targeted liposomes triggered the mitochondrial apoptotic pathway by lower production of reactive oxygen species (ROS) (63.58 vs 84.95 fluorescence intensity), reduced mitochondrial membrane potential and releasing of cytochrome c (68.66 vs 51.13 ng/mL). The results of this study indicated that Tf-targeted 5FU liposomes can be employed as promising nanocarrier for the delivery of drugs to cancer cells.